Identificação de microalgas de água doce: construção de banco de dados e avaliação de interações planctônicas através de MALDI-TOF MS - Mello, Rodrigo Ventura de (Universidade Federal de São Carlos, 2023)
Freshwater microalgae constitute a very diverse group with major ecological importance. However, the delimitation of species in some groups remains inconclusive. The absence or difficulty of recording sexual reproduction in the group implies the need to use other species concepts in addition to the biological concept. The integrative approach, which includes morphological, chemotaxonomic, biomolecular analyses, and physiological and ecological data, is proving increasingly important for a better delimitation of microalgae species. The inclusion of the ecological concept of species in the integrative taxonomy allows a better understanding of the functional diversity of these organisms. Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) is a tool with potential for distinguishing strains and species of microalgae, but databases with reference spectra of microalgae are nonexistent. Thus, we implemented a database with 23 axenic strains and tested its ability to identify strains and species of microalgae in an open-source software. The identification by spectra similarity showed a satisfactory ability to differentiate strains and species, even with cultures performed under different abiotic conditions. We also compared the MALDI-TOF MS spectra of 18 strains of closely related species grown in axenic conditions with the spectra of the same strains in different treatments with two bacteria, to integrate ecological data – of species interaction – in the specific delimitation of a family of coccoid green microalgae. Strains of A. densus and A. fusiformis showed similar responses of metabolite production when cocultured with bacteria. Two strains, CCMA-UFSCar 131 and 024, were shown to be possibly a new species and a case of misclassification, respectively. The spectra database can be of great help in the rapid identification of microalgae. Together with the ecological data, the identification by MALDI-TOF MS can help in the complex specific delimitation of freshwater green microalgae.
Freshwater microalgae identification: database assembly and evaluation of planktonic interactions with MALDI-TOF MS
Keywords: Delimitação Específica; Identificação; MALDI-TOF; Interações ecológicas; Taxonomia; Specific delimitation; Identification; MALDI-TOF; Ecological Interactions; Taxonomy; CIENCIAS BIOLOGICAS::ECOLOGIA